Nonmelanoma skin cancer in mountain guides: high prevalence and lack of awareness warrant development of evidence-based prevention tools (Swiss Medical Weekly, 2016)
AIMS OF THE STUDY: Nonmelanoma skin cancer (NMSC) is the most common cancer in Switzerland and Europe. The main causative factor is exposure to ultraviolet radiation, which puts outdoor workers in general at a higher risk of developing NMSC than indoor workers. However, few studies have clinically examined the risk of developing NMSC to outdoor workers, especially mountain guides. We aimed to investigate the prevalence of NMSC and corresponding precancerous lesions, and the associated risk behaviour of mountain and ski guides in order to develop future prevention programmes. METHODS: We conducted a cross-sectional study including mountain and ski guides from southern Germany, who underwent a full-body skin check-up by a dermatologist. We assessed their NMSC awareness and risk behaviour using a paper-based questionnaire. RESULTS: Of the 62 state-certified mountain and ski guides (55 men, 7 women; mean age 52.9 ± 13.4 years) included in this study, 27 (43.5%) were diagnosed with NMSC or its premalignant stages. In addition, 59.7% of the participants expressed the opinion that their protection from ultraviolet radiation exposure needs to be improved; 83.6% requested further information on NMSC, and 48.5% had never undergone a skin check-up or consulted a dermatologist before. CONCLUSIONS: Mountain and ski guides are at a high risk for developing NMSC. Their unmet medical needs indicate an underestimation of NMSC prevalence, which is usually based on reports by insurance companies, and offer the chance for developing evidence-based awareness and prevention tools that can be promoted to individuals with other outdoor jobs.